Bacterial Metabolism-Initiated Nanocatalytic Tumor Immunotherapy - Wu, Wencheng; Pu, Yinying; Gao, Shuang; Shen, Yucui; Zhou, Min; Yao, Heliang; Shi, Jianlin (Nano-Micro Letters, 2022)
The low immunogenicity of tumors remains one of the major limitations of cancer immunotherapy. Herein, we report a bacterial metabolism-initiated and photothermal-enhanced nanocatalytic therapy strategy to completely eradicate primary tumor by triggering highly effective antitumor immune responses. Briefly, a microbiotic nanomedicine, designated as Cu2O@ΔSt, has been constructed by conjugating PEGylated Cu2O nanoparticles on the surface of an engineered Salmonella typhimurium strain (ΔSt). Owing to the natural hypoxia tropism of ΔSt, Cu2O@ΔSt could selectively colonize hypoxic solid tumors, thus minimizing the adverse effects of the bacteria on normal tissues. Upon bacterial metabolism within the tumor, Cu2O@ΔSt generates H2S gas and other acidic substances in the tumor microenvironment (TME), which will in situ trigger the sulfidation of Cu2O to form CuS facilitating tumor-specific photothermal therapy (PTT) under local NIR laser irradiation on the one hand. Meanwhile, the dissolved Cu+ ions from Cu2O into the acidified TME enables the nanocatalytic tumor therapy by catalyzing the Fenton-like reaction of decomposing endogenous H2O2 into cytotoxic hydroxyl radicals (·OH) on the other hand. Such a bacterial metabolism-triggered PTT-enhanced nanocatalytic treatment could effectively destroy tumor cells and induce a massive release of tumor antigens and damage-associated molecular patterns, thereby sensitizing tumors to checkpoint blockade (ICB) therapy. The combined nanocatalytic and ICB therapy results in the much-inhibited growth of distant and metastatic tumors, and more importantly, induces a powerful immunological memory effect after the primary tumor ablation. Highlights: 1 Novel-designed microbiotic nanomedicine capable of targeting hypoxic tumor sites. 2 First paradigm of bacterial metabolism-initiated and photothermal therapy-enhanced nanocatalytic therapy for ablating tumors and inducing immunogenic cell death. 3 Strong antitumor immunity activation for abscopal tumors therapy.